2017
DOI: 10.5797/jnet.cr.2016-0093
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Carotid Artery Stenosis Complicating Scleroderma Treated by Carotid Artery Stenting

Abstract: Objective: We treated a patient with carotid artery stenosis complicating scleroderma by carotid artery stenting (CAS) and achieved satisfactory dilation. Since scleroderma was suspected to have induced carotid artery stenosis, we report the case with a review of the literature. Case Presentation:The patient was a 75-year-old woman diagnosed with scleroderma 8 years before. She thereafter developed polymyositis, liver cirrhosis, and stenosis of the bilateral internal carotid arteries; as progression of sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In 2011, YoheiIchimura et al described a case of SSc in a 50-year-old Japanese woman with ulnar artery stenosis, which was evaluated by magnetic resonance angiography and diminished by the bosentan treatment [2]. In 2017, Rin Shimozato et al reported a 75-year-old woman with carotid artery stenosis suspected to have been induced by SSc who was treated by carotid artery stenting (CAS) [9]. Our patient is a further case of clinical macro-vessel involvement in SSc.…”
Section: Case Pescriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, YoheiIchimura et al described a case of SSc in a 50-year-old Japanese woman with ulnar artery stenosis, which was evaluated by magnetic resonance angiography and diminished by the bosentan treatment [2]. In 2017, Rin Shimozato et al reported a 75-year-old woman with carotid artery stenosis suspected to have been induced by SSc who was treated by carotid artery stenting (CAS) [9]. Our patient is a further case of clinical macro-vessel involvement in SSc.…”
Section: Case Pescriptionmentioning
confidence: 99%
“…There have been case reports linking the presence of anticentromere antibodies to large and medium vessel involvement. Anticentromere antibodies, smoking and drinking, older age, dyslipidemia, diabetes mellitus, and obesity are risk factors for developing macroangiopathy in SSc [9]. Anti-cardiolipin antibody (ACL) is another factor affecting large vessels and involves thrombus formation.…”
Section: Case Pescriptionmentioning
confidence: 99%